Lactose tolerance in lambs with rotavirus diarrhoea. Issue 2 (February 1981) - Ferguson, A; Paul, G; Snodgrass, D R
Abstract : It has been suggested that lactose malabsorption is an important factor in producing the diarrhoea of acute rotavirus infection. Accordingly, the lactose tolerance of gnotobiotic newborn lambs, infected with lamb rotavirus, has been investigated by clinical studies and tissue enzyme assays. Although lactase activity is low in affected areas of the small intestine, rotavirus infected lambs are not lactose intolerant as assessed by the measurement of reducing substances in the faeces, or by the clinical effects and blood glucose levels after a 5.8 mmol (2 g)/kg lactose load on the second day post-infection. Lactose intolerance could be demonstrated by using extremely high (29.2 mmol (10 g)/kg) doses of lactose, three or four times the normal dietary lactose intake. These experiments suggest that lactose-containing feeds (such as maternal milk) are not necessarily contraindicated in patients or animals with rotavirus diarrhoea.